Using an integrated information system to reduce interruptions and the number of non-relevant contacts in the inpatient pharmacy at tertiary hospital - Binobaid, Saleh; Almeziny, M.; Fan, Ip-Shing (Elsevier, 2016)
Patient care is provided by a multidisciplinary team of healthcare professionals intended for high-quality and safe patient care. Accordingly, the team must work synergistically and communicate efficiently. In many hospitals, nursing and pharmacy communication relies mainly on telephone calls. In fact, numerous studies have reported telephone calls as a source of interruption for both pharmacy and nursing operations; therefore, the workload increases and the chance of errors raises. This report describes the implementation of an integrated information system that possibly can reduce telephone calls through providing real-time tracking capabilities and sorting prescriptions urgency, thus significantly improving traceability of all prescriptions inside pharmacy. The research design is based on a quasi-experiment using pre-post testing using the continuous improvement approach. The improvement project is performed using a six-step method. A survey was conducted in Prince Sultan Military Medical City (PSMMC) to measure the volume and types of telephone calls before and after implementation to evaluate the impact of the new system. Beforehand of the system implementation, during the two-week measurement period, all pharmacies received 4466 calls and the majority were follow-up calls. Subsequently of the integrated system rollout, there was a significant reduction (p > 0.001) in the volume of telephone calls to 2630 calls; besides, the calls nature turned out to be more professional inquiries (p > 0.001). As a result, avoidable interruptions and workload were decreased.
Keywords: Telephone call; Workload; Interruptions; Tracking system; Medication errors